The validity of the Physical Literacy in Children Questionnaire in children aged 4 to 12 - Yucui Diao; Li Wang; Sitong Chen; Lisa M. Barnett; Emiliano Mazzoli; Inimfon A. Essiet; Xiaofen Wang; Lei Wang; Yaping Zhao; Xuanxi Li; Jing Li (BMC, 2024)
Abstract Background Given the growing evidence on the health benefits associated with physical literacy (PL), it is necessary to develop sound measures to assess the levels of PL in children. The Physical Literacy in Children Questionnaire (PL-C Quest) is the first self-report pictorial-based scale to assess children's perceived PL. It has good validity and reliability in Australian children aged 7 to 12 years, but little is known in younger children and in other cultural contexts. The aim of this study was to examine the validity and reliability in an expanded age range. Methods A total of 1,870 Chinese children (girls, n = 871; 46.6%), aged 4 to 12 years (M = 8.07 ± 2.42) participated in validity testing. Structural equation modeling with the Weighted Least Squares with Mean and Variance approach was used to assess construct validity. The hypothesized theoretical model used the 30 items and four hypothesized factors: physical, psychological, social and cognitive capabilities. Multigroup confirmatory factor analysis was used to assess sex and age group (4-6 years, 7-9 years and 10-12 years) measurement invariance. Internal consistency analyses were conducted using polychoric alpha. A random subsample (n = 262) was selected to determine test-retest reliability using Intra-Class Correlations (ICC). Results All items except one (moving with equipment-skateboarding) loaded on sub-domains with λ > 0.45. The hypothesized model had a good fit (CFI = 0.954, TLI = 0.950, RMSEA = 0.042), with measurement equivalence across sex and age groups separately. Internal consistency values were good to excellent (overall: α = 0.94; physical: α = 0.86; psychological: α = 0.83; social: α = 0.81; cognitive: α = 0.86). Test-retest reliability was adequate to excellent (overall: ICC = 0.90, physical: ICC = 0.86, psychological: ICC = 0.75, social: ICC = 0.71, cognitive: ICC = 0.72). Conclusion The Chinese version of the PL-C Quest is valid and reliable for testing the self-reported PL of Chinese children aged 4 to 12. This study provides the first evidence of validity for this tool in children aged 4-6 years and also evidence that the PL-C Quest would be a meaningful instrument to assess PL in Chinese children.